Emerging Approaches in Glioblastoma Treatment: Modulating the Extracellular Matrix Through Nanotechnology - Miguel Horta; Paula Soares; Catarina Leite Pereira; Raquel T. Lima (Pharmaceutics)
Glioblastoma’s (GB) complex tumor microenvironment (TME) promotes its progression and resistance to therapy. A critical component of TME is the extracellular matrix (ECM), which plays a pivotal role in promoting the tumor’s invasive behavior and aggressiveness. Nanotechnology holds significant promise for GB treatment, with the potential to address challenges posed by both the blood-brain barrier and the GB ECM. By enabling targeted delivery of therapeutic and diagnostic agents, nanotechnology offers the prospect of improving treatment efficacy and diagnostic accuracy at the tumor site. This review provides a comprehensive exploration of GB, including its epidemiology, classification, and current treatment strategies, alongside the intricacies of its TME. It highlights nanotechnology-based strategies, focusing on nanoparticle formulations such as liposomes, polymeric nanoparticles, and gold nanoparticles, which have shown promise in GB therapy. Furthermore, it explores how different emerging nanotechnology strategies modulate the ECM to overcome the challenges posed by its high density, which restricts drug distribution within GB tumors. By emphasizing the intersection of nanotechnology and GB ECM, this review underscores an innovative approach to advancing GB treatment. It addresses the limitations of current therapies, identifies new research avenues, and emphasizes the potential of nanotechnology to improve patient outcomes.